Peranan asam lemak esensial terhadap perkembangan otak dan ketajaman penglihatan - Nelly Simarmata; Tiangsa Sembiring; Tri Faranita; Winra Pratita (Fakultas Kedokteran USU, 2012)
Essential fatty acids play an important role in brain development and visual acuity. Essential fatty acids are needed for optimal health, but human can not synthesize and must be obtained from food. There are two types of essential fatty acids, omega-3 and omega-6. The balance between these essential fatty acids is very important. Deficiency of these essential fatty acids in the critical period may affect the development of children in the future. Several studies have proven the importance of essential fatty acids in the period of brain development and visual acuity in childrenKeywords: essential fatty acids; brain development; visual acuity